Schizophrenia in young people and the nekrōsis of Christ - Harvey, A. E. (Theology, 2012)
This article describes the experience of a priest who has devoted the greater part of his ministry to offering companionship and community to a household of young people suffering from severe mental illness. His own description of their condition (which in due course began to affect his own spiritual state) is in terms of regression to an earlier stage of human evolution; but it has theological resonance in relation to Paul’s account of his own near-death experience in 2 Corinthians.